2003
DOI: 10.1007/s00431-003-1262-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo inv(2)(p12q34) associated with Klippel-Feil anomaly and hypodontia

Abstract: The current report of a patient with oligodontia and an inversion on chromosome 2 may aid in the identification of novel genes for oligodontia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The evidence for a recessive form of cervical vertebrae fusion is less convincing [9,10]. Some authors have reported various cytogenetic anomalies: translocation between 18q11.2 and 17q23 [16], and between 5q35 and 8q21.1 [17], pericentric inversion of 2p12-q34 [18], and mutations in PAX1, CDF6 at 8q22.1 [19] in patient with KlippelFeil syndrome, but the significance remains uncertain. The type of inheritance was not disclosed in our patient due to unknown family history.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for a recessive form of cervical vertebrae fusion is less convincing [9,10]. Some authors have reported various cytogenetic anomalies: translocation between 18q11.2 and 17q23 [16], and between 5q35 and 8q21.1 [17], pericentric inversion of 2p12-q34 [18], and mutations in PAX1, CDF6 at 8q22.1 [19] in patient with KlippelFeil syndrome, but the significance remains uncertain. The type of inheritance was not disclosed in our patient due to unknown family history.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a supernumerary cervical vertebra, a fusion of the arches of the second and third thoracic vertebrae (Th2-Th3; Figure 3a-c), a cleft formation of the vertebral arch of the first sacral vertebra (S1) and a spina bifida occulta are also present. Although dental anomalies in KFS are rarely described in the literature (Papagrigorakis et al, 2003;Barbosa & Maganzini, 2004), we suggest that the hypoplasia of the teeth, the enamel defects and the conspicuous diastemas are consistent with Klippel-Feil syndrome.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, spina bifida, menigocele, deafness or deafmuteness is frequently mentioned (Everberg et al, 1962), as well as os odontoideum (this is a separation of the odontoid process from the body of the axis; Sherk & Dawoud, 1981). Hypodontia (Papagrigorakis et al, 2003;Barbosa & Maganzini, 2004), cleft lip/palate, ocular anomalies, facial asymmetries, pterygium colli, cervical ribs, and gonadal dysplasia are also documented (Palant & Carter, 1972;Barbosa & Maganzini, 2004). Neurological problems can occur due to instability of the cervical spine (Rouvreau et al, 1998), including paralysis, hyperreflexia, pain, muscular atrophy, oculomotor defects, anesthesia and paresthesia (Resnick, 2002: 4536, 4602-6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations